2015
DOI: 10.1530/rep-14-0494
|View full text |Cite
|
Sign up to set email alerts
|

A direct action for GH in improvement of oocyte quality in poor-responder patients

Abstract: Declining female fecundity at later age and the increasing tendency for women to delay childbirth have lead to a drastic rise in the number of women seeking assisted reproductive technology. Many women fail to respond adequately to standard ovarian stimulation regimens, raising a significant therapeutic challenge. Recently, we have demonstrated that the administration of GH, as an adjunct to ovarian stimulation, has improved the clinical outcomes by enhancing the oocyte quality. However, the mechanism(s) by wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 37 publications
2
73
0
Order By: Relevance
“…The ovary can respond directly to GH because GHR are present in ovarian follicles . Alternatively, the actions of GH may be indirectly mediated by both IGF‐I and IGF‐II, which are synthesized within the ovary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ovary can respond directly to GH because GHR are present in ovarian follicles . Alternatively, the actions of GH may be indirectly mediated by both IGF‐I and IGF‐II, which are synthesized within the ovary.…”
Section: Discussionmentioning
confidence: 99%
“…However, in GH receptor (GHR) and GH‐binding protein knockout mice, IGF‐I treatment is not able to rescue either fertility or ovarian responsiveness to exogenous gonadotropins, indicating that the effect of GH is independent of IGF‐I . GH could also improve developmental potential of the preimplantation embryo by promoting GHR expression and the functional viability of mitochondria …”
Section: Introductionmentioning
confidence: 99%
“…Improving the pregnancy outcome of patients with DORs is a goal of many researchers. Weall et al have demonstrated that the use of growth hormone (GH) during the ovulation induction process can improve the ovarian response, the clinical pregnancy rate and the live birth rate of patients with DORs (18). IVF treatment together with androgen administration or a modulator in patients with DORs can improve the clinical pregnancy rate, reduce the total amount of GH used, and improve the pregnancy outcome (19).…”
Section: Discussionmentioning
confidence: 99%
“…COH causes mitochondrial abnormalities in granulosa cells of Rhesus monkeys [68]. Growth hormone improves oocyte quality and increases the number of functional mitochondria when applied as part of a COH protocol in aged women with poor ovarian response [69]. The widespread use of ART necessitates extensive studies on the effects of these techniques on oocyte quality and mitochondrial function.…”
Section: Mitochondria and Reproductionmentioning
confidence: 99%